The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1101/2020.11.20.391391
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unilateral acoustic degradation delays attentional separation of competing speech

Abstract: Hearing loss is often asymmetric, such that hearing thresholds differ substantially between the two ears. The extreme case of such asymmetric hearing is single-sided deafness. A unilateral cochlear implant (CI) on the more severely impaired ear is an effective treatment to restore hearing. The neuro-cognitive cost of listening with a unilateral CI in multi-talker situations is at present unclear. Here, we simulated listening with a unilateral CI in young, normal-hearing listeners (N = 22) who were presented wi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 61 publications
3
10
0
Order By: Relevance
“…In several studies, it has been shown that NH listeners show an increased neural response latency with increasing task demand due to lower stimulus intensity, increasing background noise or stimulus vocoding. This is the case for neural processing of continuous speech (Kraus et al, 2021; Mirkovic et al, 2019; Verschueren et al, 2021) as well as simple sounds (Billings et al, 2015; Maamor & Billings, 2017; McClannahan et al, 2019; Van Dun et al, 2016). In the current study, we observed the same effect for NH listeners: When speech understanding decreases, NH listeners showed a prominent increase in latency of the neural responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several studies, it has been shown that NH listeners show an increased neural response latency with increasing task demand due to lower stimulus intensity, increasing background noise or stimulus vocoding. This is the case for neural processing of continuous speech (Kraus et al, 2021; Mirkovic et al, 2019; Verschueren et al, 2021) as well as simple sounds (Billings et al, 2015; Maamor & Billings, 2017; McClannahan et al, 2019; Van Dun et al, 2016). In the current study, we observed the same effect for NH listeners: When speech understanding decreases, NH listeners showed a prominent increase in latency of the neural responses.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, they might allocate more effort to listen the stimulus. Listening to degraded speech (e.g., Kraus et al, 2021; Mirkovic et al, 2019; Verschueren et al, 2021) or spending more effort to listen to the stimulus (e.g., Dimitrijevic et al, 2019) affects the neural responses to continuous speech. By providing amplification, we aimed to make the peripheral activation levels as similar as possible in both groups, which motivates our choice to model the neural responses to the non‐amplified speech features for HI listeners.…”
Section: Methodsmentioning
confidence: 99%
“…The latency of the first peak increases with increasing speech rate. Increased latencies are often observed in more complex conditions with a higher task demand, like for example lower stimulus intensity, vocoded speech or speech in noise (Mirkovic et al, 2019; Verschueren et al, 2021; Kraus et al, 2020). The latency of the neural responses can also be related to neural processing efficiency (Bidelman et al, 2019; Gillis et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, it has been shown that NH listeners show an increased neural response latency with increasing task demand due to lower stimulus intensity, increasing background noise or stimulus vocoding. This is the case for neural processing of continuous speech (Mirkovic et al, 2019; Verschueren et al, 2020; Kraus et al, 2020) as well as simple sounds (Billings et al, 2015; Van Dun et al, 2016; Maamor and Billings, 2017; McClannahan et al, 2019). Our results show that this increase in latency is absent for adults with a higher degree of hearing loss (Figure 5.C).…”
Section: Discussionmentioning
confidence: 99%
“…Listening to degraded speech (e.g. Mirkovic et al, 2019;Verschueren et al, 2021;Kraus et al, 2020) or spending more effort to listen to the stimulus (e.g. Dimitrijevic et al, 2019) affects the neural responses to continuous speech.…”
Section: Stimuli Presentationmentioning
confidence: 99%